A Guerra e a construção dos inimigos do Ocidente nas franquias de jogos digitais: Battlefield, Call of Duty e Medal of Honor (2007-2012) - Moreira, Ruggiero (2020)
At the end of the 20th century it was possible to observe the birth of digital games, a medium characterized by the interactivity between the device and the operator, a relationship translated by the gameplay concept. With its vast diversity of genres and mechanics, digital games conquered more and more space in Western society, a factor that becomes noticeable to from the beginning of the 21st century with the great growth of the digital games industry, which have consolidated themselves as a product that carries economic and symbolic value. To analyze the digital games, it is necessary to understand them as products that carry a duplicity inherent to them, they are “games” inserted in the mass media. So we have to analyzes them at first as games, observing their cultural construction and concepts related to this phenomenon, in a second moment, we have to understand how they are inserted in the world market of mass communication as a medium that uses its resources (audio, visual and interactivity) to build its narratives. Among the various game categories, one that will stand out in the market will be that of First Person Shooters (FPS). Focused on the war theme, the FPS, since its beginnings, used historical events and concepts as the background of their games, the use of the Second World War as one of the main themes of the their narratives. A factor that is of paramount importance for the success of games that use the World War II as a theme, is the fact of the construction of "good guys" and "bad guys" in the representations. From the beginning of 2002 until 2015, the video game market, envisioned a growing release of themed games that had as a backdrop the war in the 21st century, also called “modern war”. Such a paradigm shift came after the terrorist attacks of September 11, 2001 and the declaration of the “War on Terror” by the United States of America. As a cultural product, digital games, build their representations by and for the society to which they are inserted, thus, the vision of the “modern war” and the “new enemies of the West” takes place through a vision Western and a product created by it. We intend, therefore, to understand how games from the Call of Duty, Battlefield, and Medal of Honor franchises build the picture about the war in the 21st century and its agents both the “western forces” and its enemies.